A Review of Nanoparticles Toxicity and Their Routes of Exposures: Transdermal delivery of insulin - Clarence S. Yah,; Sunny E. Iyuke,; Geoffrey S. Simate, (Iranian Journal of Pharmaceutical Sciences, 2012)
The new scientific innovation of engineering nanoparticles (NPs) at the atomic scale (diameter<100nm) has led to numerous novel and useful wide applications in electronics, chemicals, environmental protection, medical imaging, disease diagnoses, drug delivery, cancer treatment, gene therapy, etc.. The manufactures and consumers of the nanoparticles-related industrial products, however, are likely to be exposed to these engineered nanomaterials which have various physical and chemical properties at levels far beyond ambient concentrations. These nanosized particles are likely to increase unnecessary infinite toxicological effects on animals and environment; although their toxicological effects associated with human exposure are still unknown. To better understand the impact of these exposures on health, and how best to formulate appropriate monitoring and control strategies, this review seeks to examine various toxicological portal routes associated with NPs exposures. In fact, these ultrafine particles are capable of entering the body through skin pores, debilitated tissues, injection, olfactory, respiratory and intestinal tracts. These uptake routes of NPs may be intentional or unintentional. Their entry may lead to various diversified adverse biological effects. Until a clearer picture emerges, the limited data available suggest that caution must be exercised when potential exposures to NPs are encountered. Some methods have been used to determine the portal routes of nanoscale materials on experimental animals. They include pharyngeal instillation, injection, inhalation, cell culture lines and gavage exposures. This review also provides a step by step systematic approach for the easy identification and addressing of occupational health hazards arising from NPs.